1995
DOI: 10.1172/jci118144
|View full text |Cite
|
Sign up to set email alerts
|

Rabbit model of Lyme borreliosis: erythema migrans, infection-derived immunity, and identification of Borrelia burgdorferi proteins associated with virulence and protective immunity.

Abstract: Erythema migrans (EM), persistent skin infection, and visceral dissemination can be induced reproducibly in the adult male New Zealand White rabbit by intradermal injection of as few as 103 Borrelia burgdorferL EM was found to persist for 7±3 d. Skin culture positivity (infection) cleared within a mean of 6.7±1.4 wk after infection and similarly visceral infection was not demonstrated after 8 wk; infection-derived immunit to intradermal challenge was evident 5 mo after initial infection. The extent of the prot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
79
1
1

Year Published

1995
1995
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(86 citation statements)
references
References 28 publications
5
79
1
1
Order By: Relevance
“…Histopathologically, EM is marked by perivascular infiltration of lymphocytes and plasma cells with few macrophages and scattered mast cells (8). Similar skin lesions were reported in both monkey and rabbit models of Lyme borreliosis (9,10). In the monkey, the histopathology of EM consists of macrophage and lymphocyte infiltration, accompanied by a prominent eosinophil and an occasional basophil response (9).…”
Section: Increasing the Recruitment Of Neutrophils To The Site Of Infmentioning
confidence: 54%
See 1 more Smart Citation
“…Histopathologically, EM is marked by perivascular infiltration of lymphocytes and plasma cells with few macrophages and scattered mast cells (8). Similar skin lesions were reported in both monkey and rabbit models of Lyme borreliosis (9,10). In the monkey, the histopathology of EM consists of macrophage and lymphocyte infiltration, accompanied by a prominent eosinophil and an occasional basophil response (9).…”
Section: Increasing the Recruitment Of Neutrophils To The Site Of Infmentioning
confidence: 54%
“…In the monkey, the histopathology of EM consists of macrophage and lymphocyte infiltration, accompanied by a prominent eosinophil and an occasional basophil response (9). In the rabbit EM lesion, the infiltration is a mixed lymphocyte population with occasional macrophages and plasma cells (10). Apparently, EM results from the inflammatory response triggered by spirochete replication and develops to contain infection.…”
Section: Increasing the Recruitment Of Neutrophils To The Site Of Infmentioning
confidence: 99%
“…B. burgdorferi sensu stricto strain B31 was used in the experiments presented in this report and will be referred to as B. burgdorferi strain B31 throughout this manuscript. Virulent B. burgdorferi was originally isolated from infected mouse or rabbit tissue as previously described (26). The term "passage" and the corresponding number refers to the number of times a B31 B. burgdorferi log phase culture was transferred to fresh BSK II media.…”
Section: Methodsmentioning
confidence: 99%
“…The term "passage" and the corresponding number refers to the number of times a B31 B. burgdorferi log phase culture was transferred to fresh BSK II media. Previous studies indicated that B. burgdorferi strain B31 maintained infectivity in rabbits and mice to at least passage 47 and 85, respectively (26). The avirulent B. burgdorferi strain B31 (American Type Culture Collection [ATCC] 35210, Rockville, MD) has been passaged several hundred times in vitro in our laboratory and is noninfectious for both mice and rabbits (13,26).…”
Section: Methodsmentioning
confidence: 99%
“…Chez l'animal, seuls le lapin et le singe Rhésus sont décrits comme dévelop-pant un érythème migrant suite à l'inoculation de Borrelia (Philipp & Johnson, 1994 ;Foley et al 1995).…”
Section: Manifestations Cliniquesunclassified